Using ICT Programs to Support Students with Dyslexia in Aquiring Literacy - Shofiyatul Huriyah (ETERNAL (English Teaching Journal), 2018)
Mastering reading and writing skills as the key priority for students who experience developmental disorders reading and writing or dyslexia. Learning language for dyslexic students is not easy, dyslexic students have difficulty processing language components, especially in reading and writing. Reading and writing begin at an early age, and continue into elementary school. Students learn to read and write by memorizing and repeating letters and words. However, the fact is that this method cannot always be taught for dyslexic students. Students with dyslexia are very different from students in general, they learn differently at very different levels. Some students need more support from the people around them. Dyslexic students are easily saturated if they are invited to learn to read and write. To overcome this problem it is necessary to use the Information and Communication Technology (ICT) program in learning, this program is based on digital, so that it can help dyslexic students in the field of literacy. The use of ICT programs is very supportive of literacy skills and can provide benefits to them, they can learn independently in education, work, and home environment. These programs allow dyslexic students to have the opportunity to access almost all texts. Using the program  provide opportunities for dyleksia students to continue learning, and practice so that it is hoped that dyslexic students are able to succeed in writing and reading activities.